Pneumatic separation system for collected seedlings using subdivided air streams - Jiang, Delong; Gu, Song; Chu, Qi; Yang, Yanli; Gu, Meizhang; Yang, Yi (International Journal of Agricultural and Biological Engineering, 2022)
To adhere to the needs of automated supply of collected seedlings for mechanized grafting and cutting machines for enhancing their operational efficiency, herein, a separation system that uses subdivided air streams to separate the collected seedlings is developed. The separation system comprises a feeder for supplying collected seedlings, a seedling separator that uses subdivided air streams, a picking belt for the separated seedlings, a delivery unit for the separated seedlings, a pneumatic unit, and a control unit. To investigate the complete performance of separation, picking, and delivery of the separation system, several separation experiments were conducted to separate the collected Anthurium seedlings. The results show that the consistency of the moving direction of seedlings floated by subdivided air streams in the separation container and the moving direction of the picking belt have a significant effect on the picking of the separated seedlings by the picking belt. Moreover, the seedling supply timing of the feeder has a significant effect on the stability of the collected seedling separation rate during continuous separation. When this timing is such that the percentage of separated seedlings is 70%, the separation rate of continuous separation operation is 2.24 plant/s (the separation productivity is 8060 plants/h) with 0.12 CV. The operating conditions are 0.5 MPa separation pressure, 0.5 s nozzle operation time, and 60 mm seedling thickness in the separation container. Moreover, the staying times of the collected seedlings separated in the separation container are less than 2.5 min.Keywords: grafting, cuttings, pneumatic separation system, continuous separation, subdivided air stream, separation speedDOI: 10.25165/j.ijabe.20221502.6835Citation: Jiang D L, Gu S, Chu Q, Yang Y L, Gu M Z, Yang Y. Pneumatic separation system for collected seedlings using subdivided air streams. Int J Agric & Biol Eng, 2022; 15(2): 84–92.